Recovery Mentors as continuing professional development trainers for better recognition of the epistemic value of the experiential knowledge and improved access to recovery-oriented practices - Jean-François Pelletier; Larry Davidson; David Gaulin; Jonathan Bordet (AIMS Press, 2019)
Objectives: To lay the groundwork for the arrival of Recovery Mentors (RMs) in some of its multidisciplinary teams, a Continuing Professional Development (CPD) conference was organized in a large public agency in the province of Quebec, Canada. The aim was to come up collectively with recommendations to improve access to recovery-oriented care and services for this vulnerable population by recognizing the epistemic value of their lived experience. Methods: A series of workshops were organized among health professionals to reflect on their practice and to discuss the role of RMs for improving epistemic equity and recognition of the experiential knowledge. In preparation for these workshops participants completed the Recovery Self-Assessment (RSA). The RSA is a 32-item questionnaire designed to gauge the degree to which programs implement recovery-oriented practices, which should notably include RMs in multidisciplinary teams (five-point Likert scale: 1= strongly disagree ; 5 = strongly agree). The interactive workshops were hosted by RMs as trainers who first shared their lived experience and understanding of recovery. Results: Eighty-height of the 105 participants completed the RSA. The highest score on the RSA was for the item Staff believe in the ability of program participants to recover (mean = 4.2/5). The lowest score was for the item People in recovery are encouraged to attend agency advisory boards and management meetings (mean = 2.2/5). Based on the average inter-item correlation, a reliability test confirmed an excellent internal consistency for the French RSA scale, with a Cronbach's Alpha of .9. Means and standard deviation for each item of the RSA questionnaires were calculated. The results did not differ by participant characteristics. Results to the RSA and results from the workshops that were co-hosted by RMs were reported in the plenary session and further discussed. The workshops, the RSA and the whole CPD conference raised awareness among health professionals about stigmatizing attitudes and epistemic inequity in actual service provision. Conclusion: RMs could be invited to actively participate and attend advisory boards and management meetings more frequently and on a more regular basis for ongoing quality improvement towards better access to recovery-oriented practices. This CPD conference has shown the acceptability and feasibility of including RMs as trainers for better recognition of the epistemic value of the experiential knowledge of recovery. They can help health professionals to recognize and better appreciate service users as knowers and potential contributors to knowledge.